Enhancing Students' Vocabulary Mastery through the Look-Say Method in Junior High School - Serina, Serina; Hamidiyah, Aisyah; Utomo, Dhafid Wahyu (Journal of Linguistics, Literacy, and Pedagogy, 2024)
This study was aimed to investigate students’ English vocabulary mastery improvement using the Look-Say method. The quasi-experimental was used as the research method and the sample was the seventh-grade students of the Islamic School in Dahu Banten. The instruments in this research were the pre-test and post-test. The content validity was used to test the item tests validity and the IBM SPSS Statistics 23 application with the Cronbach Alpa formula was used to test the reliability. The findings showed that there was an increase in mean scores from pre-test to post-test: the experimental class’s average score increased from 38.97 to 91.03, while the control class’s average score increased from 40.09 to 59.11. The Independent T-test from students’ score of the post-test was 0.00, which indicates a significant difference between the experimental class and the control class. Therefore, it can be concluded that the Look-Say method can enhance the seventh-grade students at Islamic School in Dahu Banten